Lussazioni pure di caviglia - Nobile, F.; Scipio, D.; Mangiavacchi, M.; Russo, L.; Sampieri, L.; Ciampalini, L. (Lo Scalpello - Journal, 2018)
PURE ANKLE DISLOCATION Pure ankle dislocation is a rare event in Orthopaedic and Traumatology Emergency Departments. As it constitutes an emergency, prompt reduction is mandatory to reduce the risk of neurovascular impairment. In most cases, high energy trauma (motor vehicle or sports accident) is the cause of pure tibiotalar dislocation, as it leads to forced plantarflexion and inversion or eversion of the foot; young men are more often involved and predisposing anatomical factors as well as ligamentous laxity could favour dislocation. The following article provides a critical review of the current literature in order to outline the epidemiology, treatment, outcome and possible complications of pure ankle dislocation.